Description and analysis of a terrorist group: Boko Haram.: An example of the (inter) national risks produced by a failed state. - FUSTER LEAL, Rubén (Journal of the Spanish Institute for Strategic Studies, 2022)
Boko Haram has been the bloodiest terrorist group of the last decade and its actions have triggered a great global media impact, even though they take place in Nigeria. Included on the salafi jihadist terrorism, this group is an important franchise to global jihadism. Furthermore, the current Boko Haram´s dissemination could cause further destabilisation of the fragile Occidental Sahel region. Even so, Boko Haram´s speech, social support and strategy are closely linked to the internal situation of Nigeria. For this reason, it is necessary to analyse Boko Haram’s context. In this article we are going to describe Boko Haram’s beginning, ideology and objectives, strategy, leadership, structure and composition, as well as the committed attacks and victims. Next, we will do an analysis of this terrorist group, focusing on its context. In addition, Boko Haram will be analysed as factor of destabilization of Nigeria and Sahel Occidental region. Finally, we will suggest some conclusions and suggestions.